Determinants of Tourism Village Development on Community Welfare in Tabanan district - Mahendra Putra, I Putu Herry; Utama, Made Suyana (Jurnal Ekonomi Kuantitatif Terapan; Vol 18 No 1 (2025): Vol. 18, No. 1, FEBRUARI 2025 (pp.1-149), 2025)
The tourism sector is one of the sources of foreign exchange income for a country. One of the provinces in Indonesia that has the largest tourism-leading sector is Bali Province. Through the development of tourism villages and community-based tourism, it is expected to improve the welfare of the community. The purpose of this study was to analyze the effect of community participation, government role, and community empowerment on tourism village development and community welfare in Tabanan Regency. The population of this study is the community involved in tourism village development in Tabanan Regency, namely Pinge Tourism Village and Jatiluwih Tourism Village. The sampling technique used was non-probability sampling with a purposive sampling technique, and we obtained a sample of 138 observational samples. Data analysis techniques were used in the study using a structural equation model (SEM) with partial least squares (PLS) software. The results of the analysis show that community participation, government role, and community empowerment have a positive and significant effect on community welfare through tourism village development in Tabanan Regency. The community and government can maintain tourism village development to improve the welfare of rural communities and the facilities needed to meet the needs of tourist villages.